Die konvensie van Sandrivier as die afsluiting van die Groot Trek - Storm, J. M. G. (Hervormde teologiese studies, 1989)
The Sandriver Convention as the termination of the Great Trek The participants of the Great Trek had a clear and well sighted goal; To errect and build a free and sovereign state. In 1851, when the Brittish had to fight wars against the Xhosas as well as against the Basutu, Andries Pretorius, leader of the Voortrekkers in the Transvaal, forced the English government to recognice the territory north of the Vaalriver as independent. It happened on the 17th January 1852 when the Sandriver Convention was signed. Here, the major goal of the Great Trek was achieved, when the first Voortrekker state, recognised by the Brittish and known as the Zuid Afrikaansche Republiek, was born.